Results of Randomized Comparative Efficacy Study of Iron Deficiency Anemia Management in Children with Iron III Hydroxide Polymaltose Complex and Iron Sulfate - Ivan V. Fisyun; Tatyana A. Kuznetsova; Yana A. Tkacheva; Elena V. Yakubova (Union of pediatricians of Russia, 2022)
Background. The guidelines on selection between iron preparations, iron sulfate (IS) and iron III hydroxide polymaltose complex (HPC), for iron deficiency anemia (IDA) management in pediatrics are contradictory. Objective. The aim of the study is to compare efficacy and safety of iron (III) HPC and IS for IDA treatment in children. Materials and methods. Randomization of children (aged from 1 month to 18 years) with IDA into 2 therapeutic groups was implemented in 2019-2020. on pediatric districts of children's city outpatient's clinic: IS dosage of 3 mg/kg/day and iron (III) HPC dosage of 5 mg/kg/day. Hemogram monitoring was performed every 14 days. The efficacy was compared according to the rate of Hb level increase, erythrocytes indices, and serum ferritin (SF) level at the recorded moment of Hb normalization. For the safety - the rate of adverse effects. Results. 65 children with IDA were included in the study and randomized into 2 groups, the median age was 2.3 years (1st; 3rd quartile = 1.1; 4.3). Hb level increase was comparable in both groups (0.34 (0.23; 0.48) g/L/day and 0.24 (0.21; 0.30) g/L/day, р = 0.891). IS is more effective than iron (III) HPC in terms of average red blood cell volume by the time of Hb normalization (83.5 (80.0; 86.7) fl against 80.7 (79.0; 82.0) fl, р = 0.006), and mean cellular hemoglobin content (28.9 (SD = 2.0) pg against 27.4 (SD = 1.8) pg, р = 0.004). The timing of SF levels normalization did not differ. Adverse effects to iron III HPC treatment occurred 5.5 times more frequently than to IS (p = 0.0001). Conclusion. The efficacy of IS and iron III HPC at standard doses is comparable. The advantage in tolerability and recovery of erythrocytic indices justifies the feasibility of using IS preparations in the first line of treatment for children with IDA.